(untitled) (Bioscience Journal, 2022)
Ants are important components of food webs in several ecosystems. In anthropic areas, they can be used as bioindicators of the environmental impacts caused by many factors or in the evaluation of the dynamics of the recovery of an area after a certain disturbance. In this context, ants can be used as bioindicators in studies on the evaluation of environmental disturbances caused by pesticide use. Thus, the present work investigated the environmental impacts caused by the application of the insecticides chlorpyriphos and thiamethoxam and the herbicide metsulfuron-methyl in the community of ants in wheat crop (Triticum aestivum L.). The data were collected by pitfall traps and Berlese funnels. A Principal Response Curve was used for a relative abundance analysis. In addition, diversity index and richness were calculated for ant communities. The presence of six families, 11 tribes, 15 genera, and 19 morphospecies of ants belonging to the guilds of fungivorous, omnivorous, and predaceous ants were observed in the soil of the wheat crop. The insecticides chlorpyriphos and thiamethoxam reduced the richness, diversity, and relative abundance of ants of all the guilds on the surface and inside the soil. The effect of the herbicide metsulfuron-methyl on the community of ants was lower than the impact of the insecticides on these insects.